The Ratio of Live Load to Dead Load on I-Girder Prestressed Concrete Bridges Using Theoretical and Numerical Analysis - Sanjaya, Rudi; Aminullah, Akhmad; Suhendro, Bambang (Universitas Ibn Khaldun Bogor, 2025)
Bridges are essential connectors between regions separated by geographical barriers, facilitating transport across national, provincial, and district roads. In Indonesia, the prestressed I-girder concrete bridge (PCI-Girder) is a widely used design, particularly for spans between 20 and 45 meters. These bridges are a common choice in toll road development projects, part of the national strategic plan to promote regional equity and support economic growth. Seismic loads influence the PCI-Girder bridge superstructure less, allowing consistent design practices concerning cross-sectional dimensions and concrete quality relative to span length. However, girder profiles and spacing variations have become prominent in Indonesia, significantly impacting load distribution and bridge performance. This study examines the effects of live load relative to dead load on PCI-Girder bridges with girder spacing variations of 1850 mm, 2100 mm, and 2450 mm for spans ranging from 20 to 45 meters, based on SNI 1725-2016 standards. Using theoretical calculations in Microsoft Excel and numerical analysis with Midas Civil software, the study highlights the influence of girder spacing on effective area, strand requirements, camber, and beam stress post-tensioning. The findings indicate that increased girder spacing enhances the effective area of composite sections but requires larger strand areas and higher concrete strength. Moment analysis reveals that for spans over 20 meters, dead load moments dominate live load moments, whereas for 20-meter spans, live load moments are more significant. As span length increases, the influence of dead loads becomes more prominent. The 2450 mm spacing variant also shows higher live-to-dead load moment and shear force ratios than other configurations, providing insights for optimizing PCI-Girder bridge designs.